Using a web-based platform to apply the Nutrition Care Process and capture nutrition outcomes and patient satisfaction in a student-led dietetic outpatient clinic: a pilot study - Rajshri Roy; Julia Sekula; Constantina Papoutsakis (Bond University, 2021)
Evaluation of health care services utilising student providers is essential in determining effectiveness, quality of care, and student performance. We investigated the effectiveness of a student-led dietetic clinic in patient satisfaction and nutrition outcomes. A mixed-methods observational cohort pilot study utilising surveys and focus groups was conducted in outpatient student-led dietetic clinics at a university used for student education. Nutrition care and outcomes were documented using the Nutrition Care Process Terminology (NCPT) in a web-based platform. The patient satisfaction survey (n=88) of patients attending student-led dietetic clinics revealed an overall ranking of 4.0 (mean score 4.33 ± 0.34) out of 5, ranging between "very satisfied" and "satisfied." Survey and focus group data showed that the highest satisfaction rates were for students' interpersonal skills (4.80 ± 0.43). Fourteen patients attended >2 consultations. 23.5% of the patients resolved their nutrition diagnoses, and an average weight loss of 2.2 kg per patient was achieved (n = 8). Positive patient satisfaction ratings, combined with improved nutrition outcomes, support the value of student-led clinics as an education and health care delivery modality. These findings are worthy of exploring further on a large scale.